A Note on the Optimal EOQ for Announced Price Increases in the Infinite Horizon - LIM, Andrew (Institutional Knowledge at Singapore Management University, 2005)
Huang et al. (2003) used the Cesaro limit of a savings function to determine the optimal special order in an EOQ model with single announced price increases over an infinite horizon. In this note, we point out that the savings function is not Cesaro summable. More importantly, no limiting argument for the cost function d(t,Qs) as t approaches infinity is necessary at all given that this function is periodic for which it suffices to optimize the integral of the function over any given period.